2021
DOI: 10.1016/j.janxdis.2021.102460
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19-related anxiety: The role of obsessive-compulsive symptom dimensions, anxiety sensitivity, and body vigilance

Abstract: The novel coronavirus disease (COVID-19), first detected in December of 2019 and declared a global pandemic in March of 2020, continues to pose a serious threat to public health and safety worldwide. Many individuals report anxiety in response to this threat, and at high levels, such anxiety can result in adverse mental health outcomes and maladaptive behavioral responses that have consequences for the health of communities more broadly. Predictors of excessive anxiety in response to COVID-19 are understudied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
6
21
0
Order By: Relevance
“…Quarantine‐related lifestyle changes led to different unfavorable conditions such as psychosocial distress, depression, and stress. 2 , 7 COVID‐19 pandemic‐related studies reported higher levels of anxiety similar to the previous investigations in earlier pandemics, such as the outbreak of the severe acute respiratory syndrome‐related to coronavirus in 2003. In an analysis of the Chinese population, 53.8% of individuals reported moderate‐to‐severe psychosocial impact associated with the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…Quarantine‐related lifestyle changes led to different unfavorable conditions such as psychosocial distress, depression, and stress. 2 , 7 COVID‐19 pandemic‐related studies reported higher levels of anxiety similar to the previous investigations in earlier pandemics, such as the outbreak of the severe acute respiratory syndrome‐related to coronavirus in 2003. In an analysis of the Chinese population, 53.8% of individuals reported moderate‐to‐severe psychosocial impact associated with the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 83%
“… Turkey Europe General population N.A. Collectivism Ojalehto et al, 2021 438 N.A. USA North America General population 30.29 Individualism Eşkut et al, 2021 247 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, continent was added in the meta-analysis as a potential moderator to assess the moderating effect of different countries. In most studies conducted in North America, females had higher levels of COVID-19 related fear and anxiety than males (Camacho et al, 2020; Grande and Doyle-Baker, 2021 ; García-Reyna et al, 2021 ; Gélinas et al, 2021 ; Landa-Blanco et al, 2021 ; Lee et al, 2020 ; Pérez-Fuentes et al, 2020 ; Ojalehto et al, 2021 ). In addition, studies conducted in Europe, female's COVID-19 related fear and anxiety levels were higher ( Bakioğlu et al, 2020 ; Kaçoğlu et al, 2021 ; Morales-Rodríguez, 2021 ; Orrù et al, 2021 ; Tsipropoulou et al, 2020 ; Ypsilanti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess COVID-19 anxiety may be a unique type of health anxiety, one of the unique symptoms of which is the fear of infection by COVID-19. According to previous studies on the COVID-19, anxiety, disgust, intolerance of hesitation, anxiety sensitivity, and fear of physical arousal are the predictors of excess anxiety triggered by COVID-19 (22,23).…”
Section: Discussionmentioning
confidence: 94%